an Implementation of Ethno-STEM to Enhance Conceptual Understanding - Marufi, Marufi; Ilyas, Muhammad; Winahyu, Winahyu; ikram, Muhammad (Al-Jabar: Jurnal Pendidikan Matematika, 2021)
The Ethnomathematics-based STEM (Ethno-STEM) approach is currently one of the topics that receive attention to improve students' conceptual understanding. This study aimed to investigate the effect of the Ethno-STEM approach on students’ conceptual understanding. This study utilized quantitative data with a quasi-experiment. One class was chosen through a simple random sampling technique. The instruments used were conceptual understanding tests and an observation sheet of learning implementation. The data analysis techniques used were descriptive and inferential analysis, as well as the criteria of effect in instruction. Key findings point towards the importance of building an Ethno-STEAM approach that supports the conceptual understandings. Identification of critical elements of the teachers’ supports led to recommendations for teacher preparation for mathematical learning. We see the study as having value for research and practice by raising a new approach related to Ethno-STEAM and demonstrating the need for the development of theory to explain the relationships identified by this study. Key Words: